Engineering structures and functions of mesenchymal stem cells by suspended large-area graphene nanopatterns. (26th August 2016) - Kim, Jangho; Bae, Won-Gyu; Park, Subeom; Kim, Yeon Ju; Jo, Insu; Park, Sunho; Jeon, Noo Li; Kwak, Woori; Cho, Seoae; Park, Jooyeon; Kim, Hong Nam; Choi, Kyoung Soon; et al.
Abstract: Inspired by the hierarchical nanofibrous and highly oriented structures of natural extracellular matrices, we report a rational design of chemical vapor deposition graphene-anchored scaffolds that provide both physical and chemical cues in a multilayered organization to control the adhesion and functions of cells for regenerative medicine. These hierarchical platforms are fabricated by transferring large graphene film onto nanogroove patterns. The top graphene layer exhibits planar morphology with slight roughness (∼20 nm between peaks) due to the underlying topography, which results in a suspended structure between the nanoridges. We demonstrate that the adhesion and differentiation of human mesenchymal stem cells were sensitively controlled and enhanced by the both the nanotopography and graphene cues in our scaffolds. Our results indicate that the layered physical and chemical cues can affect the apparent cell behaviors, and can synergistically enhance cell functionality. Therefore, these suspended graphene platforms may be used to advance regenerative medicine.